Toxicity of Bacillus thuringiensis subsp. israelensis to adult Aedes aegypti mosquitoes. - Klowden, M J (1983)
Adult female Aedes aegypti mosquitoes were killed by the parasporal crystals of Bacillus thuringiensis subsp. israelensis (ONR-60A) when the crystals were introduced into the insect midgut as an enema. The 50% lethal dose for intact parasporal crystals was 0.21 microgram/mg of mosquito (wet weight), and for solubilized crystals the 50% lethal dose was 0.04 microgram/mg. These values were compared with 50% lethal concentrations in a free-feeding larval mosquito bioassay of 0.018 and 1.28 microgram/ml for intact and solubilized crystals, respectively. Preparations from B. thuringiensis subsp. kurstaki were ineffective against both adult and larval mosquitoes. An adult mosquito bioassay is suggested as a direct means of screening potential mosquito control agents.